2015
DOI: 10.1039/c4ra12542h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 7a-phenyl-1a,7a-dihydro-benzopyrano[2,3-b]azirin-7-ones via photoisomerization reaction

Abstract: An environmentally friendly and novel protocol has been developed for the synthesis of 7a-phenyl-1a,7a-phenyl-benzopyrano[2,3-b]azirin-7-ones in moderate to high yieldsviathe photoisomerization of 4-phenyl-5-(2-hydroxyphenyl)isoxazoles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…In our group, various complicated fused-polyheterocyclics, e.g., 2 H -phenanthro­[9,10- c ]­pyrazoles, dibenzo [ f , h ]­[1,2,4]­triazolo­[3,4- b ]­quinazolines, 7a-phenyl-1a,7a-dihydro­benzo­pyrano­[2,3- b ]­azirin-7-ones, poly­benzo­quinazolines, benzo­[ c ]­furo­[2,3- a ]­xanthenone, 14 H -dibenzo­[ a,c ]-xanthen-14-one, benzo­[ e ]-chromeno­[2,3- g ]­indol-13­(1 H )-one, and C5-modified pyrimidine and pyrimidine nucleoside derivatives were synthesized via photochemical process. In 1996, Silva et al reported that the photo-oxidative cyclization of ( E )-2-styryl-chromones at ambient temperature for 30–50 days in the open air gave 12 H -benzo­[ a ]­xanthene-12-ones in moderate yields (Scheme ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In our group, various complicated fused-polyheterocyclics, e.g., 2 H -phenanthro­[9,10- c ]­pyrazoles, dibenzo [ f , h ]­[1,2,4]­triazolo­[3,4- b ]­quinazolines, 7a-phenyl-1a,7a-dihydro­benzo­pyrano­[2,3- b ]­azirin-7-ones, poly­benzo­quinazolines, benzo­[ c ]­furo­[2,3- a ]­xanthenone, 14 H -dibenzo­[ a,c ]-xanthen-14-one, benzo­[ e ]-chromeno­[2,3- g ]­indol-13­(1 H )-one, and C5-modified pyrimidine and pyrimidine nucleoside derivatives were synthesized via photochemical process. In 1996, Silva et al reported that the photo-oxidative cyclization of ( E )-2-styryl-chromones at ambient temperature for 30–50 days in the open air gave 12 H -benzo­[ a ]­xanthene-12-ones in moderate yields (Scheme ).…”
mentioning
confidence: 99%
“…15a Later on, [Cp*RhCl 2 ] 2 was successfully applied to the same substrates with slightly elevated temperature to give ortho-hydroxyl-substituted diaryl ketone product in better yield 98% (path c). 15b In our group, various complicated fused-polyheterocyclics, e.g., 2H-phenanthro[9,10-c]pyrazoles, 16 18 polybenzoquinazolines, 19 benzo-[c]furo[2,3-a]xanthenone, 20 14H-dibenzo[a,c]-xanthen-14one, 21 benzo[e]-chromeno[2,3-g]indol-13(1H)-one, 22 and C5modified pyrimidine and pyrimidine nucleoside derivatives 23 were synthesized via photochemical process. In 1996, Silva et al reported that the photo-oxidative cyclization of (E)-2-styrylchromones at ambient temperature for 30−50 days in the open air gave 12H-benzo[a]xanthene-12-ones in moderate yields (Scheme 2).…”
mentioning
confidence: 99%
“…Our mechanistic proposal is based on the photoinduced homolysis of the N–O single bond of the isoxazole substrate analogous to previously reported studies. The following step deviates as C–C bond rotation renders a reactive conformation of the resulting biradical ( Int-1 ) in which the oxygen-centered radical can abstract a hydrogen atom from the nearby methyl group via a six-membered transition state (Scheme ). The intermediary carbon-centered radical rapidly forms an azirine species ( Int-2 ) via C–N bond formation.…”
mentioning
confidence: 90%
“…Although many decades have passed since the initial synthetic report by Ullman and Singh (Scheme A), renewed interest in this intriguing and highly atom-efficient process has arisen over the last years. Recent synthetic studies by Opatz and co-workers for instance exploited the intermediacy of photochemically generated azirines by their intermolecular conversion to densely functionalized pyrroles, whereas Zhang and co-workers demonstrated their intramolecular trapping via phenols to afford tricyclic aziridines (Scheme B). Spectroscopic studies using 3,5-dimethylisoxazole as substrate additionally provided insights into the formation of nitrile ylide intermediates as reported by Nunes and Reva .…”
mentioning
confidence: 99%
“…To date, there are many methods including step-wise synthesis, 6 pyranone ring cyclizations, 7 and conjugate addition reactions, 8 which have been reported to effectively construct the chromone core structures. Although these approaches have been used frequently for the synthesis of chromone family members, they are not applicable for the synthesis of 2-imino-substituted or 2-amino-substituted chromenones.…”
Section: Introductionmentioning
confidence: 99%